Detecting stress injury (fatigue fracture) in fibular cortical bone using quantitative ultrashort echo time‐magnetization transfer (UTE‐MT): An ex vivo study. (30th July 2018) - Jerban, Saeed; Ma, Yajun; Nazaran, Amin; Dorthe, Erik W.; Cory, Esther; Carl, Michael; D'Lima, Darryl; Sah, Robert L.; Chang, Eric Y.; Du, Jiang
Abstract : Bone stress injury (BSI) incidents have been increasing amongst athletes in recent years as a result of more intense sporting activities. Cortical bone in the tibia and fibula is one of the most common BSI sites. Nowadays, clinical magnetic resonance imaging (MRI) is the recommended technique for BSI diagnosis at an early stage. However, clinical MRI focuses on edema observations in surrounding soft tissues, rather than the injured components of the bone. Specifically, both normal and injured bone are invisible in conventional clinical MRI. In contrast, ultrashort echo time (UTE)‐MRI is able to detect the rapidly decaying signal from the bone. This study aimed to employ UTE‐MRI for fatigue fracture detection in fibula cortical bone through an ex vivo investigation. Fourteen human fibular samples (47 ± 20 years old, four women) were subjected to cyclic loading on a four‐point bending setup. The loading was displacement controlled to induce −5000 ± 1500 μ‐strain at 4 Hz. Loading was stopped when bone stiffness was reduced by 20%. Fibula samples were imaged twice, using UTE‐MRI and micro‐computed tomography (μCT), first pre‐loading and second post‐loading. After loading, the macromolecular fraction (MMF) from UTE‐MT modeling demonstrated a significant decrease (12% ± 20%, P = 0.02) on average. Single‐component T 2 * also decreased significantly by BSI (12% ± 11%, P = 0.01) on average. MMF reduction is hypothesized to be a result of collagenous matrix rupture and water increase. However, faster T 2 * decay might be a result of water shifts towards newly developed microcracks with higher susceptibility. Despite this good sensitivity level of the UTE‐MRI technique, the μCT‐based porosity at a voxel size of 9 μm was not affected by loading. UTE‐MRI shows promise as a new quantitative technique to detect BSI. Abstract : For the first time, ultrashort echo time‐magnetic resonance imaging (UTE‐MRI) was used to detect bone stress injury (BSI) via an ex vivo study. BSI was induced through cyclic loading until 20% stiffness reduction in 14 fibular samples. The macromolecular fraction (MMF) from UTE‐magnetization transfer (MT) modeling demonstrated significant reduction after the loading session.